Digital Stakeholder Engagement in Social Media: Toward an Integrative Conceptual Framework - Indriana Sularni; Sylvia Veronica Siregar (Politeknik Ganesha Medan, 2026)
The rapid development of digital technology has transformed how organizations communicate and build relationships with stakeholders. This study examines how social media and digital platforms are used in stakeholder engagement, the factors influencing the quality of digital stakeholder engagement, and the outcomes generated for organizations and stakeholders. This study employed a Systematic Literature Review (SLR) approach using the PRISMA guideline to ensure a transparent and structured review process. Using purposive sampling based on predetermined inclusion and exclusion criteria, 22 peer-reviewed journal articles published between 2021 and 2026 were selected from Emerald Insight, ScienceDirect, MDPI, Taylor & Francis, Springer, and Wiley Online Library, supported by Google Scholar and Publish or Perish. The selected articles were analyzed using qualitative thematic analysis. The findings identify three core dimensions of digital stakeholder engagement, namely digital input, engagement process, and engagement outcome. This study proposes a conceptual framework showing that stakeholder engagement in digital environments is shaped by the interaction between platform characteristics, communication quality, stakeholder interpretation, and organizational capabilities. The results also reveal that digital stakeholder engagement is multidimensional and ambivalent, as it can generate positive outcomes such as trust, reputation, participation, and transparency, while also producing skepticism, greenwashing accusations, and stakeholder polarization. This study contributes an integrative understanding of stakeholder relations in digital environments by positioning digital stakeholder engagement as a relational process rather than merely a platform-based communication practice.